Online Gambling Practices and Their Economic Impacts in Muara Sabak Timur District: A Qualitative Study in the Perspective of Islamic Economics - Arliani, Rida; Abidin, Zaenal; Yatima, Khusnul (CV. Zabags Qu Publish, 2025)
Online gambling has become a concrete threat to the economic and social stability of society, particularly in regions with low digital literacy and weak institutional oversight. This study aims to identify the forms of online gambling practices that have emerged in Muara Sabak Timur District, analyze their economic impacts on the individuals involved, and evaluate these practices through the lens of Islamic economic principles. Employing a qualitative approach with an intrinsic case study strategy, data were collected through in-depth interviews with active and former online gamblers, community leaders, and religious figures, and were thematically analyzed using NVivo software. The results reveal that online gambling is conducted through covert digital mechanisms that foster behavioral dependence, leading to financial destruction, family conflict, and psychological disturbances. No systematic intervention from local authorities was identified. An evaluative review based on “maqashid al-shariah” confirms that these practices contradict Islamic principles concerning the protection of wealth, intellect, and lineage. This study contributes to the development of a religious value-based analytical model for assessing digital economic risks and recommends community-based intervention and digital literacy policies as strategic responses to the growing prevalence of online gambling in rural societies.